CISD1 inhibits ferroptosis by protection against mitochondrial lipid peroxidation - Yuan, Hua; Li, Xuemei; Zhang, Xiuying; Kang, Rui; Tang, Daolin (Biochemical and biophysical research communications, 2016)
Ferroptosis is a form of non-apoptotic cell death originally identified in cancer cells. However, the key regulator of ferroptosis in mitochondria remains unknown. Here, we show that CDGSH iron sulfur domain 1 (CISD1, also termed mitoNEET), an iron-containing outer mitochondrial membrane protein, negatively regulates ferroptotic cancer cell death. The classical ferroptosis inducer erastin promotes CISD1 expression in an iron-dependent manner in human hepatocellular carcinoma cells (e.g., HepG2 and Hep3B). Genetic inhibition of CISD1 increased iron-mediated intramitochondrial lipid peroxidation, which contributes to erastin-induced ferroptosis. In contrast, stabilization of the iron sulfur cluster of CISD1 by pioglitazone inhibits mitochondrial iron uptake, lipid peroxidation, and subsequent ferroptosis. These findings indicate a novel role of CISD1 in protecting against mitochondrial injury in ferroptosis.